Alteration of the Methylation Status of Urokinase Plasminogen Activator (uPA) is involved in Proliferation and Invasion of Nasopharyngeal Cancer Cells - Ju-Hong Yang; Chun-Sheng Lu; Song Zhang (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2015)
The extracellular matrix degradation is the most important step in the process of tumor cell metastasis. Urokinase-type plasminogen activator (uPA) can catalyzes the conversion of the inactive zymogen plasminogen to the active broad-spectrum plasmin, which degrades a number of matrix proteins and also activates other proteases, including some matrix metalloproteinases. In this study, we evaluated that effect of methylation status of urokinase plasminogen activator (uPA) on invasion and metastasis of nasopharyngeal cancer cells. Methylation status of urokinase plasminogen activator (uPA) was detected by Methylation-specific PCR in the nasopharyngeal carcinoma cells. Reverse transcription-PCR was used to detect the expression of uPA mRNA in the nasopharyngeal carcinoma cell. Invasive and proliferation capacity of CNE2 cell was detected by using Boyden chamber Matrigel invasion assay and Cell proliferation assay after MBD2 knockdown. Our data demonstrated that uPA gene promoter hypomethylation is related to strong uPA mRNA expression in nasopharyngeal cancer cell, uPA mRNA expression was significantly reduced after MBD2 knockdown in the CNE2 cells, the proliferation and invasion capacity of CNE2 cells was significantly inhibited after MBD2 knockdown. Our data suggest that reversal of uPA gene hypomethylation will become a novel therapeutic approach for blocking nasopharyngeal cancer progression and metastatic.